KARAKTERISASI ARANG AKTIF DARI KULIT BUAH DURIAN - Abigael Todingbua’; Lasire; Jusnaeni; Sri Maharani (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Advanced materials are materials that have certain superior properties in terms of physical, chemical, mechanical and other properties. Activated charcoal has the potential to become an advanced material. Activated charcoal can be made from materials that have high cellulose and lignin content, such as durian fruit skin. The aim of this research was to determine the optimal reflux time with H3PO4solution for the carbon activation process from durian fruit skin. In this research, activation of durian peel charcoal was carried out using an activator of H3PO4 solution with reflux method. The reflux method is carried out with varying times (1, 2, 3, 4, and 5 hours). The best conditions for varying time using the reflux method are determined through the characterization of activated charcoal produced based on SNI 06-3730-1995 which includes tests for water content, volatile substance content, ash content, carbon content and iodine absorption capacity. The optimum time for activating durian peel activated charcoal by refluxing in a 5% H3PO4 solution was 5 hours where the resulting activated charcoal met characteristics of SNI standards, namely: water content 0.029%, ash content 0.71%, volatile content 22.08%, carbon content 99.27%, iodine absorption capacity 766.71 mg/g.